The structure of Romans : the argument of Paul's letter - Fowler, Paul B. (Fortress Press, 2016)
Paul did not write his letter to the Romans primarily out of doctrinal concerns. Paul B. Fowler argues that rhetorical questions in Romans 3-11 structure the argument, not as responses to criticism, but as Paul's careful guiding of the reader, and that these chapters, like the paraenesis in Romans 12-15, address specific circumstances in Rome- tensions between Jew and Gentile that aggravate the already precarious situation of the Roman congregation. The book includes an appendix on rhetorical devices and another on epistolary formulas in Paul's letters.